2015
DOI: 10.3906/biy-1406-35
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid alleviates cold-induced photosynthesis inhibition andoxidative stress in Jasminum sambac

Abstract: Salicylic acid (SA) is a signal molecule that mediates many biotic and abiotic stress-induced physiological responses in plants.In the current study the protective effects of SA on cold stress-caused oxidative damage and photosynthesis inhibition in jasmine plants (Jasminum sambac) were examined. Jasmine seedlings were pretreated with 100 µM SA for 3 days and then subjected to cold stress (4 °C) for 15 days. The amounts of superoxide radicals (O 2 -) and hydrogen peroxide (H 2 O 2 ) significantly increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…So, high water and soil Pb content have become acute environmental hazards (Silva et al 2017). Lead is spread from the environment and enters into the human body through food ingestion, water and air (Piano et al 2008;Cai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…So, high water and soil Pb content have become acute environmental hazards (Silva et al 2017). Lead is spread from the environment and enters into the human body through food ingestion, water and air (Piano et al 2008;Cai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The high accumulation of O2-and H2O2 leads to cell membrane lipid peroxidation, causing membrane damage and leakage of electrolytes. For examples, cold stress enhanced the production of malonic dialehyde (MDA) and relative electrolyte leakage in jasmine leaves, confirming the presence of oxidative stress [2]. In addition, H2O2 is subsequently converted into hydroxyl radical (HO·), which is a highly reactive oxidant in the family of ROS [29].…”
Section: Introductionmentioning
confidence: 92%
“…The sources of Pb include soldering, battery manufacturing, rubber and plastics industries, additive agent in fuel, as well as a pigment and drying agent in primer, paints and inks [1]. Then, Pb moves from the environment and enters the human body via food ingestion (65%), water (20%) and air (15%) [2,3]. Pb cannot be degraded, it is highly persistent and tends to enter the plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stomata closure, transportation, and ion uptake. Several studies carried out under laboratory and field conditions strongly suggested that salicylic acid plays an essential role in many biological responses in plants (Cai et al, 2015), especially the defense mechanism against biotic and abiotic stresses, which are responsible for poor plant growth and yield quality. Salicylic acid is held responsible for the endogenous signal used to maintain membrane integrity and mediating the hypersensitive systematic resistance against pathogen and disease attacks (Afzal et al, 1560;Baghizadeh, 2011;Gupta et al, 2013).…”
mentioning
confidence: 99%